O modelo didático do gênero comentário jornalístico radiofônico: uma necessária etapa para a intervenção didática - Silva, Carla Messias Ribeiro da (2009)
This research has as aim identify the defining genre journalism commentary radio characteristics for the purpose of building the " didactic model" of this genre, from which we propose possible activities that may enable the development of language capabilities for the production of texts belonging to this genre. The didactic model is an object descriptive that evidence the dimensions of a teachable genre. Its construction is only one step of a wider proposal on working with the teaching of genres and aims at the development of teaching sequences, arranged according to the link made between the genre, its characteristics and capabilities teachable of language (ability to action, discursive and linguistic-discursive) that learners are expected to develop. To achieve our goal, we sought to answer two questions: a) What are the defining characteristics of radio journalism comment? b) What are the characteristics of this genres teachable? This study initially presents the theoretical assumptions of sociodiscursive interactionism (BRONCKART, ss 1999/2007), the assumptions of the same order that address issues of didactic teaching of genres (DOLZ, 1995; SCHNEUWLY, 1998; DOLZ & SCHNEUWLY, 2004) and studies in the area of Journalism and Radiojornalism (MELO, 2003; BARBOSA, 2005, BARBEIRO & LIMA, 2003, among others). The corpus consists of texts of the Official Program of the Morning Service and Official of Issuing Radio Jovem Pan AM from São Paulo / SP. The analysis procedures focus on the production conditions of these texts and the architecture, surrounding the organization, the mechanisms and the mechanisms textualization. With the analysis results, we see the importance of production conditions for the formation of texts belonging to the genre radio journalistic comment, identify the defining characteristics of this genre, develop the teaching model and suggest some activities for developing a didactic sequence